MODEL KOOPERATIF TIPE TPS TERHADAP HASIL BELAJAR KONSEP PERKALIAN BILANGAN CACAH MATEMATIKA ANAK TUNARUNGU - Anjarsari, Agnes Fitri; Yulianti, Yulianti (JPI (Jurnal Pendidikan Inklusi), 2017)
One of the deaf students disorders in mathematics lesson was their understanding toward the material of the concept of multiplication of numbers count mathematics so that it had less good impact to learning mathematics result. Based on the problem, this research applied cooperative learning of Think Pair Share (TPS) type with the purpose to analyze the influence of cooperative model of TPS type toward learning the concept of multiplication of numbers count mathematics result to hearing impairment students before and after going treatment.The approach used was quantitative with pre-experiment kind and the design was one group pretest-posttest design. The data was collected by test method, observation, and documentation.The results of data analysis, shows that the use of implementation influence of cooperative learning model of Think Pair Share (TPS) type approach significantly to learning the concept of multiplication of numbers count mathematics result to deaf students in SLB-B Dharma Wanita Sidoarjo.Keywords:Think Pair Share (TPS), learning mathematics result, Deaf